2010
DOI: 10.1002/pi.2822
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of hybrid thiol‐ene/epoxy UV–thermal dual‐cured systems

Abstract: Hybrid thiol‐ene/epoxy coatings were prepared by combining thiol‐ene photo‐curable formulations with epoxy monomers, through a dual UV–thermal curing process. An increase in glass transition temperature and in storage modulus was observed for the hybrid thiol‐ene/epoxy coatings when compared with the pristine thiol‐ene UV‐cured system. Also, the bisphenol A moieties introduced into the hybrid networks during the dual‐curing process induced an increase in thermal stability of the cured materials. It has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…The heat evolved in the thiol-ene photopolymerization was also attributed as the responsible of the overlapping with epoxide homopolymerization in case of using pentallylamine as -ene monomer [18]. However, the extent of epoxide homopolymerization was even larger and could be detected when the proportion of allylic compound was only 10%.…”
Section: Study Of the Photopolymerization And Thermal Processmentioning
confidence: 95%
See 2 more Smart Citations
“…The heat evolved in the thiol-ene photopolymerization was also attributed as the responsible of the overlapping with epoxide homopolymerization in case of using pentallylamine as -ene monomer [18]. However, the extent of epoxide homopolymerization was even larger and could be detected when the proportion of allylic compound was only 10%.…”
Section: Study Of the Photopolymerization And Thermal Processmentioning
confidence: 95%
“…It has been reported that polysulfides derived from thiol-ene polymerization present some limitations in their physical/mechanical properties, particularly those related to modulus and attainment of high glass transition temperature due to the flexible core of the commercially available thiol monomers [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is acknowledged that the radicals formed during photolysis of the cationic photoinitiator [16] can also accelerate the thiol-ene condensation. The sulfide bonds formed are nucleophilic enough to react with the oxonium cations that propagate the epoxy homopolymerization (see Scheme 3), leading to the formation of stable alkylsulfonium salts, slowing down or even stopping epoxy homopolymerization [12,13,17,18]. Alkylsulfonium salts can act as latent thermal cationic initiators, resuming dark epoxy polymerization upon post-curing at a higher temperature, thus allowing the material to reach complete conversion [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another application of thiol-ene reaction is in the design of UV-curable B-stage adhesives, in combination with the cationic photopolymerization of epoxides [12,13]. Upon irradiation, the thiol-ene condensation leads to the formation of sulfide bonds (see Scheme 1) and to the photolysis of the photoinitiator, leading to the formation of a superacid capable of initiating the epoxy homopolymerization reactions (see Scheme 2).…”
Section: Introductionmentioning
confidence: 99%